2001
DOI: 10.1029/2000gl012635
|View full text |Cite
|
Sign up to set email alerts
|

Summer season land cover—Convective cloud associations for the midwest U.S. “Corn Belt”

Abstract: Abstract. Human-induced land cover modifications impact the planetary boundary layer's (PBL) thermal and moisture regimes on mesoscales. We investigate the association of croplands, forest, and the crop-forest "boundary" (CFB) with convective-cloud development (timing, amount) for three target areas (TAs) in the U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Within an area of approximately 200 x 200 km 2 , the size of a typical climate model grid box, the probability of storm initiation is about one third 85 higher over drier soils compared to wet areas. This relationship is consistent with previous studies looking at both Sahelian soil moisture 6 , and land cover in other regions [23][24] , where afternoon convection is favoured over surfaces with a greater sensible heat flux.…”
supporting
confidence: 81%
“…Within an area of approximately 200 x 200 km 2 , the size of a typical climate model grid box, the probability of storm initiation is about one third 85 higher over drier soils compared to wet areas. This relationship is consistent with previous studies looking at both Sahelian soil moisture 6 , and land cover in other regions [23][24] , where afternoon convection is favoured over surfaces with a greater sensible heat flux.…”
supporting
confidence: 81%
“…In a one-dimensional framework, fluxes of equivalent potential temperature are almost independent of Bowen ratio (as discussed by Garcia-Carreras, 2011) and it is therefore unclear, a priori, whether new convection will form over hot, dry or wet, cool surfaces. Observations have shown that new convective cells generally initiate preferentially over surfaces with locally enhanced sensible heat fluxes, that is, over warm, dry soil (Carleton et al, 2001;Negri et al, 2004;Taylor and Ellis, 2006;Wang et al, 2009); in the case of soil moisture, this implies a negative soil moisture-precipitation feedback. One reason for this is that although over wet soils the lower sensible heat fluxes reduce entrainment of low equivalent potential temperature air, which increases convective available potential energy (CAPE), the shallower convective boundary layer (CBL) with a strong lid tends to lead to higher convective inhibition (CIN; Adler et al, 2011;Garcia-Carreras et al, 2011).…”
Section: Convection and Land-surface Interaction Over West Africamentioning
confidence: 99%
“…However, the locations of the axes of CAPE and LI are located over the driest soils in the eastern portion of the study region. This shift in the patterns could be caused either by advection of lowlevel moisture that creates higher CAPE values downwind of the maximum soil moisture values or by the development of mesoscale circulation patterns that have been shown to enhance convective patterns along transition zones of surface properties, including soil moisture (Ookouchi et al 1984;Pielke and Segal 1986;Avissar and Pielke 1989;Fast and McCorcle 1991;Chang and Wetzel 1991;Emori 1998;Liu et al 1999;Pielke 2001;Carleton et al 2001). The lowest CIN values, indicating a stronger cap, are located in the northeastern portion of the study region where there are low-to-moderate soil moisture values (Fig.…”
Section: ) Nollj/sp-19 August 2001mentioning
confidence: 92%
“…The models generally indicate that the heterogeneities lead to the development of mesoscale circulation patterns (Ookouchi et al 1984;Pielke and Segal 1986;Avissar and Pielke 1989;Fast and McCorcle 1991;Chang and Wetzel 1991;Emori 1998;Liu et al 1999;Pielke 2001;Carleton et al 2001;Berbery et al 2003;Trier et al 2004;Holt et al 2006). Fast and McCorcle (1991) specifically found that the mesoscale circulation patterns develop along soil moisture boundaries.…”
Section: Introductionmentioning
confidence: 98%